Granular Activated Carbon Treatment May Result in Higher Predicted Genotoxicity in the Presence of Bromide - Krasner, Stuart W. (2016)
Certain unregulated disinfection byproducts (DBPs) are more of a health concern than regulated DBPs. Brominated species are typically more cytotoxic and genotoxic than their chlorinated analogs. The impact of granular activated carbon (GAC) on controlling the formation of regulated and selected unregulated DBPs following chlorine disinfection was evaluated. The predicted cyto- and genotoxicity of DBPs was calculated using published potencies based on the comet assay for Chinese hamster ovary cells (assesses the level of DNA strand breaks). Additionally, genotoxicity was measured using the SOS-Chromotest (detects DNA-damaging agents). The class sum concentrations of trihalomethanes, haloacetic acids, and unregulated DBPs, and the SOS genotoxicity followed the breakthrough of dissolved organic carbon (DOC), however the formation of brominated species did not. The bromide/DOC ratio was higher than the influent through much of the breakthrough curve (GAC does not remove bromide), which resulted in elevated brominated DBP concentrations in the effluent. Based on the potency of the haloacetonitriles and halonitromethanes, these nitrogen-containing DBPs were the driving agents of the predicted genotoxicity. GAC treatment of drinking or reclaimed waters with appreciable levels of bromide and dissolved organic nitrogen may not control the formation of unregulated DBPs with higher genotoxicity potencies.